The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.marpetgeo.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagenetic characteristics, evolution, controlling factors of diagenetic system and their impacts on reservoir quality in tight deltaic sandstones: Typical example from the Xujiahe Formation in Western Sichuan Foreland Basin, SW China

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that: • a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 36 publications
(48 reference statements)
2
34
0
Order By: Relevance
“…The XRD method used a Bruker D2 Phaser Diffractometer (230 V, 45 KVA from 4 to 60 2θ, step size of 2 per minute). Combined with the burial history curve of the target formation (L. Luo et al, 2019), the diagenetic evolution sequence was determined.…”
Section: Research Methods Of Diagenesismentioning
confidence: 99%
“…The XRD method used a Bruker D2 Phaser Diffractometer (230 V, 45 KVA from 4 to 60 2θ, step size of 2 per minute). Combined with the burial history curve of the target formation (L. Luo et al, 2019), the diagenetic evolution sequence was determined.…”
Section: Research Methods Of Diagenesismentioning
confidence: 99%
“…Since the theory of diagenesis was put forward, 27 a lot of studies have been carried out on sandstone and marine shale, and generally accepted results have been obtained 28‐30 . Li et al 31 indicated that the linkage of diagenesis to diagenetic structure mainly includes: impacts of mechanical compaction during burial history,effects of depositional facies and stratigraphy,chemical process of mineralogical conversions,fluid chemistry, temperature, and stress experienced during evolution 32‐35 .…”
Section: Introductionmentioning
confidence: 99%
“…The Upper Triassic Xujiahe Formation has become an essential tight gas unit over the last five decades of tight gas exploration and exploitation of the Western Sichuan Basin (Wang, Huang, Gong, Wu, & Yu, 2013). Numerous studies have been conducted on the diagenetic facies, porosity evolution, tectonic evolution, natural fractures, and sedimentary environment of the Xujiahe Formation Liu et al, 2018;Luo et al, 2019;Qin, Zhang, Zhao, & Zhou, 2018;Wu et al, 2020;Yu et al, 2017;Yu et al, 2019;Yue et al, 2018). However, the previous understanding of the Xujiahe Formation is mainly limited to the Xu4 member rather than the Xu2 sandstones.…”
mentioning
confidence: 99%
“…The location of the Sichuan Basin. (b) The tectonic feature of the Sichuan Basin (modified from Luo et al, 2019). (c) The location map of structural in the western Sichuan Basin.…”
mentioning
confidence: 99%
See 1 more Smart Citation